Development of a Character Education Model at Pondok Pesantren Riyadhul Muhibbin, Balangan Regency During The Covid-19 Pandemic - Faisal Rahman; Abdul Mun'im Amaly; Cucu Abdul Qosim (STAI Hubbulwathan Duri, 2022)
The purpose of this study is to accurately and authentically explain character building at the Pondok Pesantren Riyadhul Muhibbin in Balangan Regency, South Kalimantan Province, during the Covid-19 Pandemic, as well as the models used in the process. The qualitative descriptive method was applied in this investigation. The data for this study came from interviews with the caretaker's head, who served as the primary source of information, as well as ustadz and priests, as well as 25 students and their parents. Documentation as supporting data from the interviews and observations in the form of passive participation observations. The character education paradigm in this pesantren reflects the inspirational contribution of Tuan Guru Sekumpul, KH. Muhammad Zaini al-Banjari, a renowned figure and excellent scholar. He was made an idol for the santri so that his example, from childhood to becoming a charismatic preacher in the 1990s, might influence character formation by emphasizing akhlakul karimah, which became a common habit and formed from humanity's collective conscience.